Respon Produksi Kacang Tanah (Arachis hypogaea L.) Akibat Penggunaan Pupuk NPK dan Pupuk Mikroba - Yohanes Nong Bunga (Universitas Islam Negeri Mataram, 2018)
The production of peanut (Arachis hypogeae L.) has declined over the past five years. This has been influenced by the use of land regardless of soil fertility. This research aims to know the effect of using NPK and microbial fertilizer to peanut (Arachis hypogeae L.) production. The treatments consists of B1= microbial fertilizer, B2= NPK Fertilizer and B3= without fertilizer. These treatments were applied to Sima variety, Singa variety and Flores local cultivar. The result shows that the production of flowers and pods mostly produced by Sima variety through the use of microbial fertilizer. Besides, Flores local cultivar shows response which is not markedly different from the treatment using microbial fertilizer.